2003
DOI: 10.1016/s0008-6363(03)00355-9
|View full text |Cite
|
Sign up to set email alerts
|

Preprocedural serum levels of acute-phase reactants and prognosis after percutaneous coronary intervention

Abstract: Our study clearly supports the role of inflammation in restenosis after PCI as measured in statistically higher levels of Lp(a) and fibrinogen in patients with MACE and CRP in patients with repeat angina.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
0
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(39 citation statements)
references
References 28 publications
4
32
0
1
Order By: Relevance
“…During the past decade, CRP has emerged as a significant predictor of cardiovascular events in both healthy subjects and patients with coronary artery disease, with consistent clinical evidence. [6][7][8][9][10] Furthermore, the CRP level has been shown to be an independent predictor of future cardiovascular events, adding prognostic information to the Framingham Risk Score, to lipid screening, and to the metabolic syndrome. 19 Thus, in the area of primary prevention, the usefulness of the criterion encompassing the CRP modified ischemic heart disease risk score for global risk prediction is being increasingly recognized.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the past decade, CRP has emerged as a significant predictor of cardiovascular events in both healthy subjects and patients with coronary artery disease, with consistent clinical evidence. [6][7][8][9][10] Furthermore, the CRP level has been shown to be an independent predictor of future cardiovascular events, adding prognostic information to the Framingham Risk Score, to lipid screening, and to the metabolic syndrome. 19 Thus, in the area of primary prevention, the usefulness of the criterion encompassing the CRP modified ischemic heart disease risk score for global risk prediction is being increasingly recognized.…”
Section: Discussionmentioning
confidence: 99%
“…5 Numerous studies have incontrovertibly demonstrated the strong predictive value of high-sensitivity CRP (hsCRP) for adverse cardiac events in patients undergoing percutaneous coronary intervention (PCI) and with myocardial infarction (MI). [6][7][8][9][10] As a result, CRP is rapidly evolving into a stronger risk predictor than other novel risk factors in the setting of coronary ischemia and unstable angina. However, its predictive role and clinical application in patients undergoing coronary artery bypass graft surgery (CABG) remains controversial.…”
mentioning
confidence: 99%
“…On the other hand, clinical reports indicated a tendency to restenosis after percutaneous coronary intervention in patients with high expression of inflammatory factors (29). Furthermore, molecular biology studies have indicated that the mRNA expression levels of proinflammatory cytokines and chemokines such as IFN-␥, IL-1␤, IL-6, TNF-␣, MCP-1, and RANTES (regulated upon activation, normal T cell expressed and presumably secreted) were markedly elevated in cuff-injured arteries compared with control intact arteries (1,8).…”
Section: S6kmentioning
confidence: 99%
“…C-reactive protein, CRP) w surowicy przed zabiegiem wszczepienia stentu w stosunku do pacjentów z prawidłową jego wartością [13]. Wyniki te potwierdzili inni badacze [14][15][16][17][18][19]. Obecnie stan zapalny istniejący zarówno przed wszczepieniem, jak i po wszczepieniu stentu uznaje się za niezależny czynnik ryzyka wystąpienia restenozy.…”
Section: Mechanizm Restenozyunclassified